Factors that Affect Academic Achievement Student - Hardanti, Kurniasari Novi (AKRUAL: JURNAL AKUNTANSI, 2016)
The aim of this research is to reveal the influence of studentâs background when entered university are the entrance, the priority option to choose field of study, majoring of the high school, mathematics value in high school, and other factor is active to follow assistance toward academic achievement accounting student, that explain as value quantitative accounting and Grade Point Advantage. The population of the research is undergraduate students of the Department of Accounting, Faculty of Economy and Business, University of Brawijaya, entering in 2008, still enlisted as active student, and is having auditing practice course. The data of the research is taken by using questionnaire. The questionnaires given are 170 but only 137 which meet the criteria purposive sampling. Result of the research show that only university recruitmentâs way and active to follow assistance that has significant influence on the academic achievement for Accounting Student.